Factors associated with family planning use among refugee and host populations in Adjumani district, West Nile, Uganda: a comparative study - Roselline Achola; Lynn Atuyambe; Elizabeth Nabiwemba; Makumbi Fredrick; Christopher Garimoi Orach (BMC, 2024)
Abstract Introduction Uganda currently hosts an estimated 1.5 million refugees. The refugees have challenges in accessing family planning (FP) services in the host country. The study aimed to investigate factors associated with FP use among host and refugee populations in Adjumani district, Uganda. Methods A comparative cross-sectional study was conducted in May 2021 in three refugee settlements and their host communities in Adjumani district. A total of 1,310 respondents, (664 refugees and 646 host) were randomly selected using multistage cluster sampling and interviewed. Quantitative data were collected using structured questionnaires and analyzed using STATA V.15. Descriptive and Multivariate analysis performed. Results We found that modern Contraceptive Prevalence Rate (mCPR) was 30.2% (32.2% for host and 28.2% for refugees). Multivariate analysis showed that women who live singly (AOR = 2.25, 95%, CI: 1.56 -3.84), completed primary education [AOR = 1.65, 95% CI: 1.27-2.16], acquired skills [AOR = 2.28, 95% CI: 2.11-2.47], have the desire for another child [AOR = 3.73, 95% CI: 1.45- 9.60], have stayed in the study area between 3-5 years [AOR = 2.24, 95% CI: 1.46-3.42] were statistically significantly associated with FP use among both refugee and host populations. The key barrier to FP use by host was harassment of women and separation/divorce for not consulting the family members. Whereas amongst the refugees, they do not want to use FP methods. Conclusion Our findings revealed low FP use amongst both populations in Adjumani district. The main factors associated with FP use amongst refugee populations included marital status, level of education, type of occupation, and duration of stay in the study area whereas amongst the host is the marital status. Main reasons for not using FP methods included fear of side effects by hosts and not wanting to use FP by refugees. There is need to sensitize both communities about the benefits of FP at community level.